Black Dove, White Raven - Wein, Elizabeth (Hyperion, 2015)
Having moved to Ethiopia to avoid the prejudices of 1930s America, Emilia Menotti, her black adoptive brother Teo, and their mother Rhoda, a stunt pilot, are devoted to their new country even after war with Italy looms, drawing the teens into the conflict.